VR in Workplace Meetings: Learning from Social VR in “The Wild” - McVeigh-Schultz, Joshua; Isbister, Katherine (2020)
ABSTRACT Recent research on commercial and artistic social VR points to emerging forms of social augmentation that could have lessons for remote collaboration in the workplace. HCI has long demonstrated opportunities for supporting meetings through various forms of technological mediation. Likewise, research on VR has explored social augmentation as a form of perceptual manipulation. However, emerging design approaches and social practices in the social VR sector point to ways that XR could support new kinds of communication affordances in remote meeting contexts. We introduce the notion of creating ‘social affordances’, conceived of at the interpersonal level of analysis of the social experience itself, to shape workplace meeting social dynamics and engagement. We present examples from existing social VR, and outline a research agenda aimed at developing workplace-focused social affordances in VR. We conclude with a set of research questions that we aim to address with this work. Keywords virtual reality, social VR, meetings, social affordances, social augmentation Joshua McVeigh-Schultz San Francisco State University jmcvs@sfsu.edu Katherine Isbister University of California Santa Cruz katherine.isbister@ucsc.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).